Function f : N x N → N which satisfy
a. f ( n , n ) = n for all natural numbers n .
b. f ( n , m ) = f ( m , n ) for all natural numbers n , m
c. f ( m , n ) f ( m , n + m ) = n m + n for all natural numbers n , m
Let S = f ( 1 , 2 ) f ( 3 , 4 ) 1 + f ( 2 , 3 ) f ( 4 , 5 ) 1 + f ( 3 , 4 ) f ( 5 , 6 ) 1 + . . . . upto ∞
Find sum of all possible values of S correct upto 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used partial fraction decomposition to get S = 1 / 6 − 1 / 6 + 1 / 1 8 . This is a way to solve the problem without the help of Wolfram Alpha
Note that f ( m , n ) = m − n m f ( n , m − n )
Let g ( m , n ) = f ( m , n ) m n
Hence, 1. g ( n , n ) = n , g ( m , n ) = g ( n , m ) , g ( m , n ) = f ( m , n ) m n = m − n m f ( n , m − n ) m n = g ( n , m − n )
Now use Euclidean algorithm to show g ( m , n ) = g c d ( m , n )
So, f ( m , n ) = l c m ( m , n )
S = ∑ r = 1 ∞ f ( r , r + 1 ) f ( r + 2 , r + 3 ) 1
Hence, S = ∑ r = 1 ∞ r ( r + 1 ) ( r + 2 ) ( r + 3 ) 1
For n terms, S n = C − 3 ( n + 1 ) ( n + 2 ) ( n + 3 ) 1 where C is a constant.
Letting n = 1 , C = 1 8 1 .
So, S = 1 8 1
Problem Loading...
Note Loading...
Set Loading...
I'll assume 0 ∈ N (there are a lot of different definitions, hence I've pointed it out).
Fact 1:
f ( k , 1 ) = k , ∀ k ∈ N
Proof by induction:
Notice that f ( 1 , 1 ) = 1 .
Assume our statement is true when f ( k , 1 ) = k , where k ∈ N .
We'll prove that f ( k + 1 , 1 ) = k + 1 .
Whenever m = 1 , n = k , we have f ( k , 1 ) f ( k + 1 , 1 ) = k k + 1 ⟺ f ( k + 1 , 1 ) = k + 1 □
Fact 2:
f ( m , m + 1 ) = m ( m + 1 ) , ∀ m ∈ N
Proof:
Whenever n = 1 , we have \displaystyle \frac{f(m,m+1)}{f(m,1)}=m+1\stackrel{\text{Fact 1}}\iff f(m,m+1)=m(m+1), \:\forall m\in\mathbb N\square
Fact 2 lets us conclude that
S = f ( 1 , 2 ) f ( 3 , 4 ) 1 + f ( 2 , 3 ) f ( 4 , 5 ) 1 + ⋯ = 1 ⋅ 2 ⋅ 3 ⋅ 4 1 + 2 ⋅ 3 ⋅ 4 ⋅ 5 1 + ⋯ = 4 ! 0 ! + 5 ! 1 ! + 6 ! 2 ! + ⋯ = 1 8 1 = 0 . 0 5 5 5 5 . . . ≈ 0 . 0 5 6
The latter summation was calculated with some help from Wolfram Alpha .